Patch Antenna with Slots and Sar reduced through AMC - Oliveira Neto, Geraldo Fulgêncio de; de Salles, Álvaro Augusto Almeida (International Journal of Advanced Engineering Research and Science, 2022)
This study proposes a system consisting of a “patch”[1] dual-band antenna [2] with slots, dimensioned for 5G applications. In this device an AMC ("Artificial Magnetic Conductor") structure was inserted in order to improve the operating characteristics. The AMC plane [3] is formed using a 2 x 2 matrix of unit cells, each with a U-shape and a reconfigurable element. The results compared with an antenna without AMC indicate that the system provides SAR reduction, directivity improvement and gain increase to be discussed in the text.